A cultura do faça você mesmo como princípio da cibercutlura e a crítica da inversão da lógica da indústria cultural - Cardins, Jitana Sara da Cunha (2014)
With the emergence of the internet, the most important environment of cyberculture, we begin to observe that a certain freedom of creation performed by amateurs take up a space and a visibility that draws the attention of scholars. To conduct this research, we use as theoretical background the knowledge on culture, sub and counter culture, culture industry and cyberculture studies, participation and sharing culture.Therefore, we observe the emergence of a culture of the "do it yourself", which had its first manifestations in the hands of hackers and scientists, who explored this new territory and started to create new usage possibilities. Over time these actions have been gaining a new contour, resulting, in the long run, on the Internet as we know it.This dissertation aims to seek an understanding on the current dimension of the culture of the do it yourself on the internet, observing all its features implemented in the examples mapped.This is a qualitative research, which objectives are set on an exploratory and explanatory research, seeking to understand this phenomenon in the context of Communication.We performed a literature research accompanied by field surveys, directly on the Internet, to collect all the data needed for the analysis and clarifications. We conclude that the culture of the do it yourself is a basic principle of cyberculture and we become aware of inversion in the logic of the cultural industry, which once determined what the public would consume, and is now seeks on the public new ways to obtain profit.